Production and characterization of bioemulsifier by Parapedobacter indicus - Devale, Anushka; Sawant, Rupali; Pardesi, Karishma; Perveen, Kahkashan; Khanam, Mehrun NIsha; Shouche, Yogesh; Mujumdar, Shilpa (Frontiers in Microbiology, 2023)
In the current study, Parapedobacter indicus MCC 2546 was studied for its potential to produce bioemulsifier (BE). Screening methods performed for bioemulsifier production by Parapedobacter indicus MCC 2546 showed good lipase activity, positive drop collapse test and oil spreading activity. Furthermore, it showed maximum emulsification activity (225 EU/mL) and emulsification index (E24 50 %) at 37℃ in Luria Bertani broth at 72 h with olive oil as a substrate. The optimal pH and NaCl concentration for maximum emulsification activity was found to be 7 and 1 % respectively. Parapedobacter indicus MCC 2546, lowered the surface tension of the culture medium from 59.65 mN/m to 50.42±0.78 mN/m. Bioemulsifier produced was composed of 70 % protein and 30 % carbohydrate, which showed glycoprotein nature of bioemulsifier. Further, FTIR analysis confirmed the same. Parapedobacter indicus MCC 2546 showed catecholate type of siderophore production. This is the first report on bioemulsifier and siderophore production by genus Parapedobacter.